Transcriptome remodelling and changes in growth and cardiometabolic phenotype result following Grb10a knockdown in the early life of the zebrafish - Bridget L. Evans; Terence Garner; Chiara De Leonibus; Lily Wright; Megan Sharps; Oliver H. Wearing; Daniel M. Ripley; Holly A. Shiels; Adam F. L. Hurlstone; Peter E. Clayton; Adam Stevens (Cellular and Molecular Life Sciences)
Abstract Embryonic growth trajectory is a risk factor for chronic metabolic and cardiovascular disorders. Grb10 is a negative regulator of the main pathways driving embryonic growth. This study has characterised growth, cardiometabolic status, and the impact on co-ordination of gene expression following morpholino-induced embryonic and early larval knockdown (KD) of grb10a expression in zebrafish (Danio rerio). Grb10 knockdown was associated with increased embryonic growth and metabolic rate, and decreased heart rate in early life. Juvenile growth rate was also elevated. The transcriptome was assessed over 5 to 30 days post fertilisation, coinciding with major changes in zebrafish (ZF) maturation and development. Significant and persistent organisational and functional changes in the whole transcriptome over this time were evident, including dysregulation of multiple growth, cardiac, and metabolic pathways. In adulthood (18 months), KD ZF had greater body length and mass than controls, with elevated cardiac muscle content, an increased aerobic scope, and higher fasting glucose levels. This study demonstrates that early life disruption of a single gene in zebrafish can result in long-term transcriptomic remodelling and alterations to the adult cardiometabolic phenotype.